Analysis of paralytic shellfish poisoning toxin congeners by a sodium channel receptor binding assay - Usup, G.; Leaw, CP; Cheah, MY; Ahmad, A.; Ng, BK (Elsevier Ltd, 2004)
This study was carried out to characterize the detection and quantitation of several paralytic shellfish poisoning (PSP) toxin congeners using a receptor binding assay (RBA). This involved competitive binding of the toxin congeners against tritiumlabeled STX for receptor sites on rat brain sodium channels. Competitive binding curves were described by a four-parameter logistic equation. Half-saturation values (EC50) ranged from 4.38 nM for STX to 142 nM for GTX5. Receptor binding affinity was in the order STX . GTX1/4 . neoSTX . GTX2/3 . dcSTX . GTX5, and this was similar to the order of mouse toxicity of these congeners. Predicted toxin concentrations from observed STXeq values and EC50 ratios relative to STX were within 20% or better of the actual concentrations used in the assay. In contrast predicted toxin concentrations using mouse toxicity ratios relative to STX did not provide a good match to actual concentrations, except for GTX1/4. This study has shown that the rat brain sodium channel RBA will provide a reliable integration of total toxicity of various PSP toxin congeners present in a sample.